Criminal Sanctions’ Reformulation in the Reclamation of the Mining Community - Faisal Faisal; Derita Prapti Rahayu; Yokotani Yokotani (Fiat Justisia: Jurnal Ilmu Hukum, 2022)
The norm of sanctions in Mining Law 2020 through irrational legislative policies can trigger criminal disparities and become a criminogenic factor. Reformulation efforts are needed in formulating sanctions regarding reclamation. This research aims to realign the purpose of criminalizing the post-mining reclamation obligation in the community mining category. The discussion is focused on the provisions reformulation for the community mining category's reclamation obligation. The problem will be researched using normative legal research methods. According to this research, the reclamation obligation sanction is an omission offense. The reclamation omission offense is both a passive law and a formal offense. Reformulation is based on the basic idea of ​​balancing the double-track system of criminal sanctions. Criminal sanctions become the last instrument if the sanctions are ignored. Action sanctions prioritize restoring post-mining environmental conditions. The criminal sanctions threat and fines in the community mining category must be lighter.